ChemInform Abstract: Natural Organic Acids Promoted Synthesis of 3, 4‐Dihydropyrimidin‐ 2(1H)‐ones/thiones under Solvent‐Free Conditions. Issue 30 (July 2015) - Thorat, Nitin M.; Thopate, Shankar R.
Abstract Malic acid is found to be an effective promoter for the Biginelli reaction under solvent free conditions and conventional heating as well as microwave irradiation conditions.